2019
DOI: 10.1007/978-3-030-31280-0_8
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Search Algorithms for App Testing

Abstract: Automated testing techniques can effectively explore mobile applications in order to find faults that manifest as program crashes. A number of different techniques for automatically testing apps have been proposed and empirically compared, but previous studies focused on comparing different tools, rather than techniques. Although these studies have shown search-based approaches to be effective, it remains unclear whether superior performance of one tool compared to another is due to fundamental advantages of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In summary, this means that EAs are not contributing substantially to gain better statement coverage in Android test generation. This result is also consistent with the study presented by Sell et al 10 for Android test generation in which single-objective and multiobjective algorithms do not perform better than random algorithms, and sometimes they even perform slightly worse.…”
Section: Rq2: What Is the Contribution Of The Nsga-ii Ea In Sapienz C...supporting
confidence: 92%
See 2 more Smart Citations
“…In summary, this means that EAs are not contributing substantially to gain better statement coverage in Android test generation. This result is also consistent with the study presented by Sell et al 10 for Android test generation in which single-objective and multiobjective algorithms do not perform better than random algorithms, and sometimes they even perform slightly worse.…”
Section: Rq2: What Is the Contribution Of The Nsga-ii Ea In Sapienz C...supporting
confidence: 92%
“…In particular, for Android test generation, in order to obtain statement coverage for a given individual, evolutionary approaches need to push the test case to a device/emulator, start the application, run test case, gather fitness information, and pull it from device/emulator. In their work, 10 Sell et al suggested that high execution costs hamper any meaningful evolution for search algorithms. In our study, we observed that the fitness evaluation might take up to 60 s for a test case, depending on its length.…”
Section: Empirical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Dynodroid [31] extends the random selection using weights and frequencies of events. Modeland search-based strategies such as COBWEB [39], SwiftHand [40], EHB-Droid [41], PUMA [42], EvoDroid [43], DroidBot [44], MobiGUITAR [45], juGULAR [46], ABE [47], Humanoid [48], Sapienz [1], Stoat [32], and MATE [9] apply model-based testing with dedicated search strategies to mobile applications. The type of model and search strategy is different in each approach and can range from simple to sophisticated solutions.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, trial-and-error experiments to empirically determine a suitable configuration of NSGA-II was not a viable option due to the high costs of executing search-based test generation approaches for apps (cf. [7,9]). In contrast, a fitness landscape analysis generally aims for an analytical understanding of the search problem that should help to improve the heuristic.…”
Section: Introductionmentioning
confidence: 99%